The Effects of Macroeconomic Variables and Corporate Financial Performance on Stock Prices of Palm Oil Companies in Indonesia - Putri, Pebrika Yudha; Achsani, Noer Azam; Pranowo, Koes (Jurnal Manajemen dan Agribisnis, 2019)
Palm oil commodity is still one of the largest foreign exchange contributors to the Indonesian states and remains as an attractive industry. In 2016, Indonesia was the main exporter of CPO with the highest production volume in the world. Palm oil issuers face business challenges from external and internal factors. This research was conducted to analyze whether the stock price of oil palm issuer in Indonesia was influenced by macroeconomic variables (crude oil price, exchange rate, inflation, and interest rate) and financial performance variables (DER, ROA, ROE, EPS, and AUR). This is important because if the macroeconomic variables and financial performance of the company have an impact on the company's performance reflected in the stock price movement of the issuer, this will be an important consideration for investors to take decisions. The results of this research using panel data regression (2010-2016 with quarter data) indicated that only one macroeconomic variable of Exchange Rate that had a negative significant effect on the price of palm oil stock while the financial performance variables in this research affecting the palm oil stock price significantly were DER, ROA, ROE, EPS, EPS t-1, and Stock Price t-1. All variables used in this research can represent the influence of the stock price of palm oil by 99.21%.